LOOKING AT ENGLISH NATIONAL EXAMINATION 2016 IN INDONESIA: A PROSPECT OF BLOOM’S REVISED TAXONOMY - Candra Jaya (Bandar Lampung University (UBL), 2016)
The primary purpose of this qualitative study was to investigate two dimensions of Cognitive domains, which consist of Cognitive process dimension and Knowledge dimension, in Bloom’s Revised Taxonomy by gauging each category of thinking skills utilized on 35 reading comprehension questions in the English National Examination 2015/2016 of Senior Secondary School in Indonesia. The categories of Cognitive process dimension consist of six including remember, understand, apply, analyze, evaluate, and create; and, of Knowledge dimension consist of four including factual, conceptual, procedural, and meta-cognitive. Model questions of Bloom’s Revised Taxonomy, Structure of Cognitive process dimension, Structure of Knowledge dimension, and Taxonomy Table were deployed as instruments in this study. The findings, out of six categories of thinking skills, of Cognitive process dimension uncovered that, out of 35 reading questions, 22 questions, which indicated 63%, appeared as remember category, 10 questions, which indicated 28%, appeared as understand category, and 3 questions, which indicated 9%, appeared as analyze category. Meanwhile, the findings, out of four knowledge categories, of Knowledge dimension uncovered that, out of 35 reading questions, 27 questions, which indicated 77%, appeared as factual knowledge, 6 questions, which indicated 17%, appeared as conceptual knowledge, and 2 questions, which indicated 6%, appeared as procedural knowledge.